System jednolitego rynku wewnętrznego Unii Europejskiej a Ukraina z perspektywy układu stowarzyszeniowego - Cieśliński, Aleksander (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2015)
This article is part of a bigger paper that is going to be published in this volume and the following one. Its purpose is to analyze current situation of Ukraine after the entering into force of Association Agreement. The idea of its author is to juxtapose the legal system of EU single internal market and its rules with the set of obligations regarding introduction of free movement of goods, persons, services and capital in coming years steaming from this Agreement. The reason to concentrate on this particular part of EU-Ukraine relations is the fundamental meaning of above rules both for the modernization and future development of Ukraine and its future capability to apply for real membership. In order to evaluate this the first article analyzed the legal construction of the Association Agreement itself. The second one will be concerned on the convergence between the regulatory frameworks of Ukraine and the EU seen as a way to its integration into the European economic legal space.
Keywords: umowa stowarzyszeniowa; Ukraina-UE; Jednolity rynek wewnętrzny; harmonizacja